Measuring patient satisfaction: three years' data and experience of using a validated patient questionnaire. (August 2015) - Challenor, Rachel; Perry, Ryan
A validated patient satisfaction questionnaire for use in sexual health clinics was run throughout the southwest region (the UK) three times over three years (13 clinics in January 2012 and 12/13 clinics in January 2013 and the same 12 clinics again in January 2014). The questionnaire covered aspects of pre-appointment, performance of health care professionals, facilities, privacy, respectful communication, information on leaving and overall experience. Data from 1750 questionnaires are presented with means and 95% confidence intervals. Patients under the age of 25 were less likely to rate care as excellent and/or very good ( P = 0.001) compared with those above the age of 25. There was no difference in satisfaction levels according to gender or sexual orientation. Time in clinic was strongly associated with satisfaction levels – those in clinic for over 90 min expressed less satisfaction ( P = 0.0005). We hope that other clinics may find it useful to use the validated questionnaire to look at their own performance and compare it against the southwest data. The main value is to identify areas where changes to service delivery could translate into improved practice and improved satisfaction, particularly where performance is identified as less than the 95% confidence intervals.